2022
DOI: 10.1128/mbio.01926-22
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mediated Inactivation of the Transcriptional Repressor RcrR is Responsible for Uropathogenic Escherichia coli’s Increased Resistance to Reactive Chlorine Species

Abstract: How do pathogens deal with antimicrobial oxidants produced by the innate immune system during infection? Uropathogenic Escherichia coli (UPEC), the most common etiological agent of urinary tract infections (UTIs), is particularly exposed to infiltrating neutrophils and, therefore, must counter elevated levels of the antimicrobial oxidant HOCl to establish infection. Our study provides fundamentally new insights into a defense mechanism that enables UPEC to fend off the toxic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Proteins constitute for >50% of the cellular macromolecules and are known to rapidly react with HOCl ( Hawkins and Davies, 2019 ). Numerous studies in different HOCl-treated bacterial species revealed the strong upregulation of the heat shock regulon, indicating an accumulation of misfolded proteins and supporting the idea that proteins are the major targets of HOCl ( Groitl et al, 2017 ; Gray et al, 2013b ; Sultana et al, 2022 ; Thakur et al, 2019 ; Tung et al, 2020 ; Hillion et al, 2017 ). Similarly, H 2 O 2 can cause substantial protein aggregation as the result of methionine and cysteine oxidation ( Imlay, 2008 ).…”
Section: A Year At the Forefront Of Bacterial Defense Systems Against...mentioning
confidence: 64%
See 3 more Smart Citations
“…Proteins constitute for >50% of the cellular macromolecules and are known to rapidly react with HOCl ( Hawkins and Davies, 2019 ). Numerous studies in different HOCl-treated bacterial species revealed the strong upregulation of the heat shock regulon, indicating an accumulation of misfolded proteins and supporting the idea that proteins are the major targets of HOCl ( Groitl et al, 2017 ; Gray et al, 2013b ; Sultana et al, 2022 ; Thakur et al, 2019 ; Tung et al, 2020 ; Hillion et al, 2017 ). Similarly, H 2 O 2 can cause substantial protein aggregation as the result of methionine and cysteine oxidation ( Imlay, 2008 ).…”
Section: A Year At the Forefront Of Bacterial Defense Systems Against...mentioning
confidence: 64%
“…Given the physiological significance of HOX exposure during infection, research in this field is rapidly evolving even though we are still far away from understanding the full picture of HOX defenses in bacteria. The bacterial response and defense strategies are expected to be critical for their ability to survive the immune cell attack, as reported by several recent studies ( Sultana et al, 2022 ; Fritsch et al, 2023 ; Foik et al, 2022 preprint). Moreover, independent studies confirmed that the presence of functional oxidative stress defense systems positively affects pathogen colonization in the host, emphasizing their importance for pathogenesis ( Peng et al, 2020 ; Dahl et al, 2017 ; Hryckowian and Welch, 2013 ; Bessaiah et al, 2019 ).…”
Section: Future Prospectsmentioning
confidence: 83%
See 2 more Smart Citations
“…RclR also responds strongly to reactive chlorine compounds (Parker et al, 2013), and since the HOCl-responsive E. coli transcription factor NemR also appears to detect HOSCN (Kostyuk et al, 2022), we suspect that many cysteine-dependent HOCl-sensitive regulators in bacteria (da Cruz Nizer et al, 2020) may also respond to HOSCN, but this remains to be determined. A homolog of RclC has recently been characterized in uropathogenic E. coli (UPEC) and has been implicated in aiding with membrane stability when cells are exposed to HOCl (Sultana et al, 2022), but the mechanism by which it does so remains unknown.…”
Section: Reiter Et Al Observed Bactericidal Effects Of Milk On Differ...mentioning
confidence: 99%